SPECIFIC FEATURES OF INTERPRETATION OF MYOCARDIAL PERFUSION SINGLE-PHOTON EMISSION COMPUTED TOMOGRAPHY WITH COMPUTED TOMOGRAPHIC ABSORPTION CORRECTION - A. A. Ansheles (Вестник рентгенологии и радиологии)
Objective: to study the capabilities of a hybrid single-photon emission computed tomography/computed tomography (SPECT/CT) system during myocardial perfusion imaging study, to evaluate the impact of absorption correction (AC), and to reveal factors influencing the contribution of AC to the diagnostic result of the study.Material and methods. The study included 167 patients who underwent myocardial perfusion SPECT with and without CT AC. Differences between AC and non-AC studies were visually analyzed; the results of the analysis were used to form groups of visual differences. The supposed factors influencing the contribution of AC were studied, by assigning visual differences to a particular group.Results. The possible variants of the impact of AC were described in the baseline scintigrams. AC made a significant contribution in 68% of cases. With AC, the perfusion defects visible during non-AC study recovered in 80% of these cases. The factors predicting substantial differences between the AC and non-AC studies included weight, end diastolic volume, male sex, patients with small focal perfusion defects and transient ischemia, and inadequate injected activity. Factors, such as body mass index, large perfusion defects, CT subsystem and orbit settings, and time from the injection of a radiotracer to the initiation of a study, had no substantial impact on the contribution of AC. During AC studies, SRS and transient ischemic dilatation were significantly higher than during non-AC studies, requiring a shift of standard criteria. There were some methodical features of interpretation of myocardial perfusion SPECT using CT correction.Conclusion. Myocardial SPECT with AC enhances the diagnostic value of the technique, simplifies the interpretation of myocardial perfusion SPECT, and reduces the number of falsepositive and questionable results.